"Sultan among Hindu kings": Dress, titles, and the islamicization of Hindu culture in Vijayanagara - Wagoner, Phillip B. (The journal of Asian studies, 1996)
The author challenges the enduring stereotype of the Vijayanagara empire of early modern South India as "a Hindu state" that preserved itself in the face of growing Islamic presence in the subcontinent. It is his contention that Hindu culture at Vijayanagara was in fact deeply transformed by its interaction with Islamic culture. One of the most profound instances of Islamicization at Vijayanagara appears in the system of men court dress. The author explores the Islamicization of Hindu culture at Vijayanagara with special reference to dress. (DÜI-Sen)